Experimental Study of the Static Modal Analysis on Milling Machine Tool - Norlida, Jamil; A. R., Yusoff; Muhammad Hatifi, Mansor (2013)
Machine tool vibrations have great impact on machining process. Modal testing is a form of vibration testing which is able to determine the Frequency Response Function (FRF) of the mechanical test structures. In this paper, the main focus is to identify a procedure to obtain natural frequency values for machine tool components in order to establish better conditions in the cutting process on the machine tool. For this purpose, a 3D model of the machine tool’s structure is made using design software and exported to analysis software. Later on, the Finite Element Method (FEM) modal analysis was used to obtain the natural frequencies. The model is evaluated and corrected through an experimental modal test. In the experiment, the machine tool vibration is excited by impact hammer and the response of excited vibration is recorded. In the end, the res ult of both FEM and experimental shows a good consistency in comparison.